Therapeutic aspects of tolerance - Waldmann, H; Cobbold, S; Fairchild, P; Adams, E (Elsevier, 2001)
The immune system is naturally unresponsive to 'self' antigens. Improved knowledge of mechanisms underlying self tolerance is giving rise to a new generation of immunosuppressive agents, that can exploit these mechanisms and so reduce the nature and level of medication that needs to be given long-term to control diseases where the immune system does harm.